Games for Psychological Science. (28th April 2017) - Howes, Andrew
Abstract: How does the cognitive system, as a whole, act to generate behaviour? A crucial requirement for science aimed at answering this question is that any empirical paradigm is developed hand in hand with robust theoretical models that explain the emergence of behavioural strategies. Complex games have the potential to be one such paradigm.